Intralabyrinthine Schwannoma: Distinct Features for Differential Diagnosis - Lee, Sun-Uk; Bae, Yun Jung; Kim, Hyo-Jung; Choi, Jeong-Yoon; Song, Jae-Jin; Choi, Byung Yoon; Choi, Byung-Se; Koo, Ja-Won; Kim, Ji-Soo (Frontiers in Neurology, 2019)
Objectives: The aim of this study was to delineate the clinical and laboratory features suggestive of intralabyrinthine schwannoma (ILS). Methods: We compared the clinical features of 16 patients with ILS, who had been diagnosed at the Seoul National University Bundang Hospital from 2003 to 2018, with those of 18 patients with symptomatic unilateral intracanalicular schwannoma and randomly selected 20 patients with definite or probable unilateral Meniere’s disease (MD). Results: Patients with ILS presented with either recurrent spontaneous dizziness/vertigo combined with auditory symptoms (n=8), isolated auditory symptoms without dizziness/vertigo (n=7), or recurrent spontaneous dizziness/vertigo without auditory symptoms (n=1). Most patients reported no improvement (n=11) or worsening (n=1) of the symptoms despite medical treatments including intratympanic (n=5) or intravenous steroids (n=2). Conventional brain MRIs failed to detect ILS in about a half of the patients (7/16, 44%). However, ILS showed a filling defect on 3-dimensional (3D) heavily T2-weighted MRIs (n=12), and nodular enhancement on 3D contrast-enhanced T1 (n=15) or FLAIR MRIs (n=13) targeted for the inner ear. Compared to MD or intracanalicular schwannoma, ILS showed mostly abnormal head-impulse tests (HITs, p=0.001). In contrast, the incidence of canal paresis did not differ among the groups (p=0.513). Conclusion: ILS may mimic MD by presenting recurrent dizziness/vertigo and auditory symptoms. ILS should be suspected in patients with recurrent audiovestibulopathy especially when 1) the duration of the dizziness is not typical for MD, 2) the patients do not respond to medical treatments, or 3) HITs are abnormal.